Babcock and Wilcox Ltd, the 'Babcock Family' and regulation 17/62: A business response to new competition policy in the early 1960s. Issue 5 (3rd July 2020) - Rollings, Neil
Abstract: This article explores through the lens of the British company Babcock and Wilcox Ltd the response of a group of European companies to the threat posed to their activities by the new EEC competition policy in the early 1960s. Regulation 17/62 was set to ban the market-sharing agreements which had been in place for many years between the companies in Europe. The article tracks their deliberations over the most suitable response that would allow market sharing to continue while minimising the risk of discovery. This rare insight into the inner discussions of cartel arrangements also highlights the role of legal advice in the solution adopted.